Ask Your Doctor? Direct-to-Consumer Advertising of Pharmaceuticals - Sinkinson, Michael; Starc, Amanda (Review of Economic Studies, 2019)
We measure the impact of direct-to-consumer television advertising (DTCA) by drug manufacturers. Our identification strategy exploits shocks to local advertising markets generated by the political advertising cycle and a regulatory intervention affecting a single product. We find evidence of significant business stealing effects among branded, advertised drugs. In addition, we show positive spillovers from drug advertisements to non-advertised competitors in the same class. We decompose the effect and show it is primarily due to new customers. Finally, we provide evidence that DTCA is cost-effective from a societal standpoint in our setting.